The Impact of Peer Group Interaction on Social Behaviour and Academic Engagement of Upper Basic School Students in Gusau Local Government Area, Zamfara State - Sule Muhammad; Murtala Aliyu (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Peer group interaction plays a significant role in shaping students’ social behaviour and academic engagement, especially at the upper basic school level where peer influence is strong. This study examined the impact of peer group interaction on the social behaviour and academic engagement of 384 upper basic school students in Gusau Local Government Area, Zamfara State. A descriptive survey design was adopted. Data were collected using the validated Peer Group Interaction, Social Behaviour, and Academic Engagement Questionnaire (PGISBAEQ) and analyzed using descriptive statistics and simple linear regression at a 0.05 level of significance. The findings revealed that peer group interaction significantly influences students’ social behaviour (R = 0.612, R² = 0.375, β = 0.612, t = 15.12, p < 0.05) and academic engagement (R = 0.658, R² = 0.433, β = 0.658, t = 17.97, p < 0.05). Positive peer interactions enhanced cooperation, respect for school rules, social skills, and motivation to participate in academic activities, while negative peer pressure occasionally resulted in minor undesirable behaviours. The study concludes that peer interaction is a strong predictor of students’ social adjustment and academic participation. It recommends structured peer-mediated learning, collaborative activities, and mentorship programmes to harness positive peer influence for improved social and academic outcomes.